Place of memory and presence: the (hi)story of the “broken heart” in Southern Africa - Carvalho, X. (Memory, Narrative and Histories Research Collective (MNH Research Collective) Seminar Series Summer 2025, 2025)
Bagamoyo is in Tanzania, in Southern Africa, and it is the place of the “broken heart” (in Swahili). During the 19th century, it was in Bagamoyo that slave traders came in from the interior of Africa to Zanzibar, becoming later the first German colonial capital in the German East Africa. In the 1960s, Bagamoyo was reconfigured into the place of the birth of a new African nation, Mozambique, being firstly a military training camp of FRELIMO, the leading Mozambican liberation struggle movement against Portuguese colonialism, and later a camp of education to train student-teachers. Those trainees went inside Mozambique, while under colonial occupation, to the liberated zones of Cabo Delgado, Niassa and Tete, to reverse illiteracy among the Mozambican population, that was up to 90%. Bagamoyo is simultaneously a legacy of colonial and anti-colonial practices, in which Portuguese, German and British colonialism had encounters over time. Through photography and oral history, calling for the notion of being then (Gray 2016, Postill 2016), I present Bagamoyo as both a place of memory (Nora 2001, Montaño 2008) and presence (Baer 2002, Edwards 2015, Morton & Edwards 2009) throughout the (hi)story of the people who was there, who experienced Bagamoyo in the 1960s-1970s, when the “broken heart” gained its new meaning: a place of African liberation. When I collected oral histories, the participants told me through photography how was Bagamoyo in those times. This is the story of the history produced until now. As an anthropologist, I could not be there, but was able of being then, at a distance, a “bodily experience” requiring episodic memories based upon the notion of body memory, but only possible due to previous ethnographic experience in the field of inquiry.